This is environmental ethics an introduction - Lee, Wendy Lynne (Hoboken, New Jersey Wiley Blackwell, 2022)
"Philosophy and the life worth living While many disciplines have a vested interest in the environment, its inhabitants and ecosystems, its biotic diversity, and its future stability, it falls to philosophy perhaps more than to any other to offer organizing concepts for a viable-actionable, livable, realistic-environmental ethic. Ethics isn't about what merely is the case, but what should be. As an organizing feature of our ways of life, moral decision-making always has one foot in the context or conditions of our present actions and another pointed toward the future. A life that lacks self-reflection concerning our place in the many contexts or roles we occupy, the impacts of our decisions on our relationships with others, human and nonhuman, present and future, is not as likely, as Socrates might have put it, to be a life worth living. Even from the point of view of simple self-interest, such a life is bound to reap more pain than pleasure, more sorrow than joy. The reason, of course, is that life on planet Earth includes more than human beings and relationships. Our self-interested motives and the consequences that follow from our actions are rarely constrained to ourselves alone. Our lives include values that reach beyond the moral, for example, the aesthetic, the economic, the social, and the civic. As our recent confrontation with the Covid-19 pandemic surely reminds us, we cannot value our own health without valuing that of others, and as the climate crisis illustrates more clearly with each firenado, tsunami, or bomb cyclone, human actions have impact well beyond single communities, regions, and countries. Every time we sit down to eat, buy a car, read a book, go on vacation-every ordinary thing we do-is woven throughout with the often invisible labors of other people, with institutions like governments, and systems of economic exchange that inform virtually every action, and with nonhuman nature, living and non-living, plant life and sentient animal. Our bodies bleed these intimate relationships; our cars run on them; our books are woven of fibers extracted from the wood of an industry that threatens several endangered species. Our aspirations are made realizable through the labor and resources of countless others, most of whom we'll never see or even know. Some are exploited in developing world cell phone cities, banana plantations, diamond mines, sneaker factories, and sweat shops. Others become characters in dystopian novels and films that explore environmental apocalypse, the consequences of uncontrollable viral outbreak, species extinctions, or war over water scarcity. In these, the life worth living is displaced by stories of hardship and survival that often seem closer that we'd like to admit to the lives of people and their communities in the world as it is. They warn us of a world we do not want, but that the trajectory of our current environmental crises promise is coming. A robust practicable environmental ethic cannot save us from some of the crises we have already set into motion, but it can help us formulate plans of action that will blunt some of the impact and, if we act with well-informed deliberation and urgency, see our way to a more sustainable and more just future. In the spirit, then, of a modestly modified version of Socrates' claim, here are some important ideas that inform this work"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Environmental ethics